Otimizando o efeito antimicrobiano da terapia fotodinâmica com fotossensibilizadores fenotiazínicos pela adição de etanol ou carreador de oxigênio - Prochnow, Emilia Pithan (2014)
Formulations of Methylene Blue (MB) and toluidine blue (TB) with ethanol or oxygen carrier were evaluated for antimicrobial effect on Pseudomonas aeruginosa biofilms. Formulations photoactivated had photosensitizers (Ps) (250 μM) diluted in PBS (pH 5.6 - sodium acetate / acetic acid), 10% ethanol (buffer:ethanol 90:10), 20% ethanol (buffer:ethanol 80:20) and perfluordecalin emulsion, buffer and triton-X100 (60: 35: 5). The controls were biofilms untreated and without photoactivation. The production of singlet oxygen was measured by photo-oxidation of 1,3-difenilisobenzofuran.The data of photo-oxidation and CFU (log10) were evaluated by One-Way ANOVA and post hoc Tukey and Dunnett, respectively. Student t-test assessed differences between the Ps in the same formulation. MB showed higher singlet-oxygen production. Buffer or etanol 10% hadn´t antimicrobial effect. Ethanol 20% reduced the bacterial viability (1.2 log10, p = 0.009). The lower mean CFU were observed with MB and ethanol 10% (P = 0.052; reduction of 2.18 log10) and 20% (P = 0.053; reduction of 2.18 log10). Microbial reductions in water MB and TB were 1.13 log10 and 1.10 log10, respectively. With carredor reductions were 1.74 and 1.70 for MB and TB, respectively. MB formulations containing ethanol are comparable to some antibiotics in treating P. aeruginosa biofilms in vitro.